Health system and patient-level factors serving as facilitators and barriers to rheumatic heart disease care in Sudan - Jeffrey G. Edwards; Michele Barry; Dary Essam; Mohammed Elsayed; Mohamed Abdulkarim; Basamat M. A. Elhossein; Zahia H. A. Mohammed; Abdelmunim Elnogomi; Amna S. E. Elfaki; Ahmed Elsayed; Andrew Y. Chang (BMC, 2021)
Abstract Background Rheumatic heart disease (RHD) remains a leading cause of morbidity and mortality in Sub-Saharan Africa despite widely available preventive therapies such as prophylactic benzathine penicillin G (BPG). In this study, we sought to characterize facilitators and barriers to optimal RHD treatment with BPG in Sudan. Methods We conducted a mixed-methods study, collecting survey data from 397 patients who were enrolled in a national RHD registry between July and November 2017. The cross-sectional surveys included information on demographics, healthcare access, and patient perspectives on treatment barriers and facilitators. Factors associated with increased likelihood of RHD treatment adherence to prophylactic BPG were assessed by using adjusted logistic regression. These data were enhanced by focus group discussions with 20 participants, to further explore health system factors impacting RHD care. Results Our quantitative analysis revealed that only 32% of the study cohort reported optimal prophylaxis adherence. Younger age, reduced primary RHD healthcare facility wait time, perception of adequate health facility staffing, increased treatment costs, and high patient knowledge about RHD were significantly associated with increased odds of treatment adherence. Qualitative data revealed significant barriers to RHD treatment arising from health services factors at the health system level, including lack of access due to inadequate healthcare staffing, lack of faith in local healthcare systems, poor ancillary services, and patient lack of understanding of disease. Facilitators of RHD treatment included strong interpersonal support. Conclusions Multiple patient and system-level barriers to RHD prophylaxis adherence were identified in Khartoum, Sudan. These included patient self-efficacy and participant perception of healthcare facility quality. Strengthening local health system infrastructure, while enhancing RHD patient education, may help to improve treatment adherence in this vulnerable population.